The incredibly human Henson Blayze - Barnes, Derrick (Viking, an imprint of Penguin Random House LLC, 2025)
In the small town of Great Mountain, Mississippi, all eyes are on Henson Blayze, a thirteen-year-old football phenom who many have wondered if he was super-human. The predominately white townsfolk have been waiting for Henson to play high-school ball, and now they're overjoyed to finally possess an elite Black athlete of their own. Until a horrifying incident forces Henson to speak out about injustice. Until he says that he might not play football anymore. Until he quickly learns he isn't as loved by the people as he thought. In that moment, Henson's town is divided into two chaotic sides when all he wants is justice. Even his best friends and his father can't see eye to eye. When he is told to play ball again or else, Henson must decide whether he was born to entertain people who may not even see him as human, or if he's destined for a different kind of greatness.